Comparison of 1D and 3D heat and mass transfer models of a counter flow dew point evaporative cooling system: Numerical and experimental study - Pakari, Ali; Ghani, Saud (International journal of refrigeration, 2019)
•A counter flow dew point evaporative cooling system is developed and investigated.•1D and 3D models of the heat and mass transfer in the cooling system are developed.•On average, the 1D model temperature predictions are 1.86% lower than the 3D model.•The 3D and 1D models predict experimental results within 8.5% and 10%, respectively.•The cooling system can reach wet-bulb effectiveness values as high as 125%. In this study, the performance of a counter flow dew point evaporative cooling system has been examined, numerically and experimentally. A one-dimensional (1D) model of the heat and mass transfer in the cooling system is presented. In order to assess the 1D model, a detailed three-dimensional (3D) model is developed. Experimental results showed that the wet-bulb effectiveness of the cooling system could reach values as high as 125%. The predicted variations of air temperature along the channels of the cooling system by both models are in fair agreement. On average, the 1D model predicts lower outlet temperatures by about 1.86% relative to the 3D model. While the computational time of the 3D model is about three orders of magnitude higher than the 1D model. The predicted outlet temperature of the cooling system by the 1D and 3D models match the experimental results within 10% and 8.5%, respectively.